Audiometric profile of children with congenital citomegalovirus infection diagnosis – Data of 9 years of a children's deafness consultation - Alves, Sílvia Fidalgo (2019)
Congenital cytomegalovirus infection is the most common congenital infection. It is estimated that 1% of newborns are infected with the virus. Because, for the most part, congenital cytomegalovirus infections manifest themselves subclinically, the major cause of non-hereditary sensorineural hearing loss may be neglected. This study intends to evaluate the prevalence of congenital cytomegalovirus infection in children observed in the Children's Deafness Consultation of the Ear Nose and Throat – Head and Neck Surgery Department of the Hospital Garcia de Orta between 2007 and 2015 and determine the hearing consequences diagnosed at the date of this paper - December 2015. In the Children's Deafness Consultation, between 2007 and 2015, regarding clinical cases of congenital cytomegalovirus infection: one case of sensorineural hearing loss, bilateral, severe to profound, was detected, currently in an auditory rehabilitation program since 5 years ago; in the remaining 11 cases, the available data reveal only changes that need follow-up, alterations in the pattern of central auditory stimulus progression, or middle ear pathology. Because the sensorineural hearing loss conferred by the congenital cytomegalovirus infection is evolutionary or fluctuating, there is a continuing need for regular audiological monitoring.